Nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material and preparation method and application thereof

Synthesize nickel molybdate nanotubes through electrospinning technology and recombining them with nickel hydroxide, which solves the problems of low energy density and poor cycle stability of existing supercapacitors, and realizes supercapacitor materials with high energy density and power density, which extends the use life.

CN119274989APending Publication Date: 2025-01-07QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411423685.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing supercapacitors have low energy density and poor cycling stability and low conductivity at high current density, limiting their application in supercapacitors.

Method used

Nickel molybdate nanotubes were synthesized through electrospinning technology and composited with nickel hydroxide material. The specific surface area and active sites of the material were improved by the water bath method, and the structure and performance of the electrode material were optimized.

Benefits of technology

It significantly improves the energy density and power density of the supercapacitor, enhances the cycling stability and charge conduction efficiency of the material, and extends the service life of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005081565030000011
    Figure HDA0005081565030000011
  • Figure HDA0005081565030000012
    Figure HDA0005081565030000012
  • Figure HDA0005081565030000013
    Figure HDA0005081565030000013
Patent Text Reader

Abstract

The invention relates to a nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material and a preparation method and application thereof.According to the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material and the preparation method and application thereof, nickel molybdate nanotubes are synthesized through an electrostatic spinning technology, then a nickel hydroxide material and a nickel molybdate nanotube material are compounded through a water bath method, and the specific surface area of the material is greatly increased; the number of active sites is increased, the specific capacity and the stability of the material are further improved, and the energy density and the power density of a capacitor can be improved through the high specific surface area and an optimized electron transmission channel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material and a preparation method and application thereof, belonging to the technical field of electrochemistry. Background Art

[0002] Supercapacitors have become an important part of modern energy storage technology with their excellent power density, long life and high charge and discharge rate. Compared with traditional batteries, supercapacitors have higher power density and faster charge and discharge rate, but their energy density is usually lower. For example, patent document CN110993364A discloses a method for preparing nickel molybdate / carbon electrode material and the prepared supercapacitor, 0.5A g -1 At a current density of 1.37 W, the specific capacitance is only 325.1 F g -1 Patent document CN112216521A discloses a nickel molybdate-nickel selenide-molybdenum selenide composite material and its preparation method and application. The nanocomposite material has a -1 At this current density, the specific capacitance is only 488.5 F g -1 Therefore, improving the energy density of supercapacitors while maintaining their excellent power density and cycle stability has become an important direction in current electrochemical energy storage research.

[0003] Nickel hydroxide (Ni(OH)2) is a promising electrode material that has attracted widespread attention due to its high specific capacitance and good cycle stability. Ni(OH)2 has a layered structure, and its electrochemical properties are greatly affected by its interlayer structure and ion migration, which makes its application in supercapacitors show excellent capacitive performance. Nickel molybdate (NiMoO4) is a new type of transition metal oxide material that has been widely studied due to its excellent conductivity and chemical stability. NiMoO4 has rich oxidation states and good conductivity, which can effectively improve the energy density of electrode materials. In addition, its unique crystal structure provides more active sites for charge storage, further enhancing its capacitive performance. However, single metal oxide electrode materials face the problems of poor cycle stability and insufficient energy density in practical applications. Ni(OH)2 may experience a decrease in electrochemical performance at high current density; and its low conductivity may limit its charge conduction efficiency in supercapacitors. NiMoO4 has stability problems during application, especially under certain specific environmental conditions, such as high current density or complex chemical environment, its stability will be affected. By combining different types of electrode materials and utilizing synergistic effects, the conductivity, stability and charge storage capacity of the material can be improved to achieve ultra-high performance supercapacitor materials. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material and a preparation method and application thereof.

[0005] The present invention synthesizes nickel molybdate nanotubes through electrostatic spinning technology, and then utilizes a water bath method to composite nickel hydroxide material with nickel molybdate nanotube material, which greatly improves the specific surface area of ​​the material, increases the number of active sites, and further improves the specific capacity and stability of the material.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material comprises the following steps:

[0008] (1) dissolving citric acid in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol at room temperature, then adding nickel nitrate and ammonium molybdate, stirring until dissolved, and finally adding polyvinyl pyrrolidone (PVP), stirring for 6-12 hours, to obtain a precursor solution for spinning;

[0009] (2) injecting the precursor solution into an electrospinning machine to prepare fibers by electrospinning, placing the obtained fibers in a muffle furnace for calcining, and cooling after the calcination to obtain nickel molybdate nanotube materials;

[0010] (3) Dispersing nickel molybdate nanotube material in water, adding nickel acetate, hexamethylenetetramine (HMTA), and sodium citrate, mixing evenly, heating in a water bath for reaction for 4-12 hours, cooling, washing, and drying to obtain nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material.

[0011] According to the present invention, preferably, in step (1), the molar ratio of nickel nitrate to ammonium molybdate is (1-2): (1-2).

[0012] According to the present invention, preferably, in step (1), the volume ratio of the molar amount of citric acid to the mixed solvent is (4-6): (5-15), unit: mmol mL -1 .

[0013] According to the present invention, preferably, in step (1), the volume ratio of N,N-dimethylformamide to anhydrous ethanol is (1-2): (1-2).

[0014] According to the present invention, preferably, in step (1), the weight average molecular weight of PVP (K90) is 1000,000-3000,000.

[0015] According to the present invention, preferably, in step (1), the molar ratio of the mass of PVP to ammonium molybdate is (0.8-1.5): (0.2-2), in units of g mmol-1 .

[0016] According to the present invention, preferably, in step (1), the volume ratio of the molar amount of nickel nitrate to the mixed solvent is (1-2): (8-12), unit: mmol mL -1 .

[0017] According to the present invention, preferably, in step (2), the electrospinning conditions are: electrospinning temperature 22-28°C, voltage 18-22 kV, ejection rate 0.6-2.0 mL h -1 .

[0018] According to the present invention, preferably, in step (2), the calcination treatment is a two-step calcination treatment, specifically, first calcining at 0.5-2°C min -1 The heating rate is raised to 250-350℃, kept at this temperature for 0.5-2h, and then heated at 0.5-2℃min -1 The temperature is raised to 450-550°C at a heating rate and maintained for 0.5-3h.

[0019] According to the present invention, preferably, in step (3), the volume ratio of the molar amount of the nickel molybdate nanotube material to water is (0.5-1.5): 60mmol mL -1 .

[0020] According to the present invention, preferably, in step (3), the molar ratio of nickel acetate, HMTA and sodium citrate is (1-2): (1-2): (0.05-1).

[0021] Most preferably, in step (3), the molar ratio of nickel acetate, HMTA and sodium citrate is 1:1:0.1.

[0022] According to the present invention, preferably, in step (3), the molar ratio of the nickel molybdate nanotube material to the nickel acetate is 1:1.

[0023] According to the present invention, preferably, in step (3), the reaction temperature of the water bath is 85-95°C.

[0024] According to the present invention, preferably, in step (3), the water bath reaction time is 10-12 hours.

[0025] According to the present invention, preferably, in step (3), the washing refers to washing with anhydrous ethanol for 3-5 times, and the drying is conventional drying.

[0026] The present invention adds citric acid or citrate in the process of preparing a spinning precursor solution and preparing a nickel hydroxide nanosheet-nickel molybdate nanotube material. The citric acid or citrate serves as both a complexing agent and a stabilizer to control the release rate of nickel ions and prevent aggregation. The pH value of the solution is adjusted at the same time to affect the morphology and crystal structure of the final product, so that the nickel hydroxide particles loaded on the obtained nickel molybdate nanotubes are more uniform and have a more regular shape. The addition of sodium citrate can promote the crystallization of nickel hydroxide, improve its crystal structure, and greatly enhance the surface activity and catalytic performance of the material.

[0027] A nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material is prepared by the method.

[0028] The nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material is used to prepare a supercapacitor as a working electrode of the supercapacitor.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. The present invention synthesizes nickel molybdate nanotubes with highly dispersed hollow nanotube morphology through electrospinning technology, and then uses a mild water bath method to composite nickel hydroxide material with nickel molybdate nanotube material. First, the nanotube structure provides a larger surface area, which helps to improve the electrochemical activity of the electrode. Secondly, the pore structure of the nanotube promotes the rapid transmission of ions in the electrolyte and improves the charge and discharge rate of the capacitor. Finally, the nanotube usually has better conductivity, which helps to improve the current density and overall performance. In addition, the structure of the nanotube is more stable during multiple charge and discharge processes, which prolongs the service life of the capacitor. In summary, the morphology structure of the present invention greatly improves the specific surface area of ​​the material, provides a large amount of active surface area, optimizes the pore structure, is conducive to the infiltration of electrolytes and ion migration, and greatly improves the energy density and power density of the capacitor.

[0031] 2. Due to its special structure and chemical composition, the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of the present invention exhibits excellent capacitance characteristics and cycle stability. The high specific surface area and optimized electron transmission channel help to improve the energy density and power density of the capacitor.

[0032] 3. The present invention utilizes a synthetic method to controllably adjust the morphology of nickel hydroxide and nickel molybdate, thereby achieving precise control of the structure and performance of the composite material. This flexibility not only helps optimize the electrochemical performance of the material, but also helps achieve large-scale preparation.

[0033] 4. The present invention prepares nickel hydroxide nanosheet-nickel molybdate nanotube material by using citrate in combination with a mild water bath method. The water bath method can provide relatively mild reaction conditions, avoid side reactions that may occur at high temperatures, and is suitable for synthesizing relatively uniform nickel hydroxide. Sodium citrate is used as a complexing agent to help improve the solubility of nickel ions and reduce aggregation, thereby obtaining more uniform nickel hydroxide particles. Under mild conditions, the addition of sodium citrate can promote the crystallization of nickel hydroxide, improve its crystal structure, and improve electrochemical performance. The traditional hydrothermal method without the addition of sodium citrate usually requires a longer reaction time, and the reaction conditions are more stringent (high temperature and high pressure), and the equipment requirements are higher. The release rate of nickel ions cannot be controlled, and the particle size and distribution of the obtained nickel hydroxide are relatively uneven. At the same time, in the hydrothermal method, the reaction conditions will cause the nickel hydroxide particles to be larger and the morphology to be relatively irregular, reducing its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 X-ray diffraction spectra of the nickel hydroxide of Comparative Example 1, the nickel molybdate of Comparative Example 2, and the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode materials (Ni(OH)2, NiMoO4, Ni(OH)2 / NiMoO4) obtained in Example 1;

[0035] Figure 2 is a scanning electron microscope image of the electrode material, wherein a is the nickel molybdate electrode material of Comparative Example 2, and b is the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Example 1;

[0036] Figure 3 are transmission electron microscope images of electrode materials, wherein a is the nickel hydroxide electrode material of Comparative Example 1, b is the nickel molybdate electrode material of Comparative Example 2, and c is the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Example 1;

[0037] Figure 4 The nitrogen adsorption / desorption and pore size distribution diagram of the nickel hydroxide of Comparative Example 1;

[0038] Figure 5 The nitrogen adsorption / desorption and pore size distribution diagram of nickel molybdate of Comparative Example 2;

[0039] Figure 6 The nitrogen adsorption / desorption and pore size distribution diagram of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Example 1;

[0040] Figure 7 CV (2 mV s) of the nickel hydroxide electrode material obtained in Comparative Example 1, the nickel molybdate electrode material obtained in Comparative Example 2, and the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material obtained in Example 1 in 3M KOH solution -1 ) curve, GCD(1Ag -1) curve graph and rate performance comparison graph, a is the CV test graph, b is the GCD test graph, and c is the rate performance comparison graph;

[0041] Figure 8 CV (different scan rates) curves and GCD (different current density) curves of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Example 1 of the present invention in 3M KOH solution, a is a CV test graph, and b is a GCD test graph.

[0042] Fig. 9 CV (different scan rates) curves and GCD (different current density) curves of the nickel hydroxide electrode material of Comparative Example 1 of the present invention in 3M KOH solution, a is a CV test graph, and b is a GCD test graph.

[0043] Fig.10 CV (different scan rates) curves and GCD (different current density) curves of the nickel molybdate electrode material of Comparative Example 2 of the present invention in 3M KOH solution, a is a CV test graph, and b is a GCD test graph.

[0044] Fig.11 CV (different scan rates) curves and GCD (different current density) curves of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Comparative Example 3 of the present invention in 3M KOH solution, a is a CV test graph, and b is a GCD test graph;

[0045] Fig.12 This is a diagram of the capacity retention rate and coulombic efficiency of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material of Example 1. DETAILED DESCRIPTION

[0046] The features of the present invention are further described below by way of examples, but the present invention is not limited to the following examples.

[0047] Example 1

[0048] The preparation method of nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material comprises the following steps:

[0049] (1) Add 5 mL of N,N-dimethylformamide and 5 mL of anhydrous ethanol to a beaker, add 5 mmol of citric acid to the above solution, stir and dissolve at room temperature, then add 1 mmol of ammonium molybdate, continue stirring, then add 1 mmol of nickel nitrate hexahydrate, after complete dissolution, add 1.0 g of polyvinyl pyrrolidone with a weight average molecular weight of 1300,000, continue stirring for 6 hours, and obtain a spinnable precursor solution;

[0050] (2) The spinnable precursor solution was transferred into a plastic syringe with a stainless steel needle in an electrospinning machine. The electrospinning conditions were as follows: the syringe needle was 18 cm away from the receiving plate, the temperature was 25 °C, the voltage was 20 kV, and the solution ejection rate was 1.5 mL h -1 After the electrospinning, the obtained samples were calcined in a muffle furnace. In order to improve the stability of the structure and prevent collapse, a two-step sintering procedure was set up, including calcining at 1 °C min -1 The temperature was raised to 300 °C at a heating rate of 1 °C min and maintained for 1 h. -1 The temperature was raised to 500°C at a heating rate and maintained for 1 h, and the obtained sample was the nickel molybdate electrode material;

[0051] (3) Weigh 1mmol of nickel molybdate sample, 1mmol of nickel acetate, 1mmol of HMTA and 0.1mmol of sodium citrate, stir them in a beaker containing 60mL of aqueous solution at room temperature for 20min, and place them in a 90℃ water bath for 8h to obtain a sample. Wash the obtained sample with deionized water and ethanol three times each and then place it in a 60℃ oven to dry for 12h. Thus, the desired supercapacitor material is obtained.

[0052] The X-ray diffraction spectrum (XRD) of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material prepared in this embodiment is as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peaks of the obtained product correspond to the standard spectrum of NiMoO4 (JCPDS No.12-0348) and the standard spectrum of Ni(OH)2 (JCPDS No.38-0175).

[0053] Scanning electron microscopy (SEM) Figure 2 As shown. Figure 2 It can be seen that the morphology of the prepared sample is that ultrathin nanosheets are uniformly loaded on hollow nanotubes, forming a synergistic system, which not only makes the elements in the composite material evenly distributed, but also enhances the redox signal and charge transfer kinetics of nickel molybdate.

[0054] Example 2

[0055] The preparation method of nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material comprises the following steps:

[0056] (1) Add 5 mL of N,N-dimethylformamide and 5 mL of anhydrous ethanol to a beaker, add 5 mmol of citric acid to the above solution, stir and dissolve at room temperature, then add 1 mmol of ammonium molybdate, continue stirring, then add 1 mmol of nickel nitrate hexahydrate, after complete dissolution, add 0.9 g of polyvinyl pyrrolidone with a weight average molecular weight of 1300,000, continue stirring for 6 hours, and obtain a spinnable precursor solution;

[0057] (2) The spinnable precursor solution was transferred into a plastic syringe with a stainless steel needle in an electrospinning machine. The electrospinning conditions were as follows: the syringe needle was 18 cm away from the receiving plate, the temperature was 25 °C, the voltage was 20 kV, and the solution ejection rate was 1.5 mL h -1 After the electrospinning was completed, the obtained sample was placed in a muffle furnace for calcination. A two-step sintering procedure was set up, including calcination at 1 °C min -1 The temperature was raised to 300 °C at a heating rate of 1 °C min and maintained for 1 h. -1 The temperature was raised to 450°C at a heating rate and maintained for 1 h, and the obtained sample was the nickel molybdate electrode material.

[0058] (3) Weigh 0.5mmol nickel molybdate sample, 0.5mmol nickel acetate, 0.5mmol HMTA and 0.05mmol sodium citrate, stir in a beaker containing 60mL aqueous solution at room temperature for 20min, place in a 75℃ water bath for 4h to obtain a sample. Wash the obtained sample with deionized water and ethanol three times each and then dry in a 60℃ oven for 12h. Thus, the desired supercapacitor material is obtained.

[0059] Example 3

[0060] The preparation method of nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material comprises the following steps:

[0061] (1) Add 5 mL of N,N-dimethylformamide and 5 mL of anhydrous ethanol to a beaker, add 5 mmol of citric acid to the above solution, stir and dissolve at room temperature, then add 1 mmol of ammonium molybdate, continue stirring, then add 1 mmol of nickel nitrate hexahydrate, after complete dissolution, add 1.1 g of polyvinyl pyrrolidone with a weight average molecular weight of 1300,000, continue stirring for 6 hours, and obtain a spinnable precursor solution;

[0062] (2) The spinnable precursor solution was transferred into a plastic syringe with a stainless steel needle in an electrospinning machine. The electrospinning conditions were as follows: the syringe needle was 18 cm away from the receiving plate, the temperature was 25 °C, the voltage was 20 kV, and the solution ejection rate was 1.5 mL h -1 After the electrospinning was completed, the obtained sample was placed in a muffle furnace for calcination. A two-step sintering procedure was set up, including calcination at 1 °C min -1 The temperature was raised to 300 °C at a heating rate of 1 °C min and maintained for 1 h. -1 The temperature was raised to 550°C at a heating rate and maintained for 1 h, and the obtained sample was the nickel molybdate electrode material.

[0063] (3) Weigh 1.5mmol nickel molybdate sample, 1.5mmol nickel acetate, 1.5mmol HMTA and 0.15mmol sodium citrate, stir in a beaker containing 60mL aqueous solution at room temperature for 20min, place in a 95℃ water bath to react for 12h, and obtain a sample. Wash the obtained sample with deionized water and ethanol three times each, and then dry it in a 60℃ oven for 12h. Thus, the desired supercapacitor material is obtained.

[0064] Comparative Example 1

[0065] A method for preparing a flower ball-shaped nickel hydroxide supercapacitor electrode material, the steps are as follows:

[0066] 1mmol nickel acetate, 1mmol HMTA and 0.1mmol sodium citrate were added to a beaker containing 60mL aqueous solution and stirred for 20min at room temperature. Subsequently, the mixed solution was placed in a 90℃ water bath for 8h. After the reaction was completed, the obtained sample was washed with deionized water and ethanol 3 times each, and then dried in an oven at 60℃ for 12h. A flower ball-shaped nickel hydroxide supercapacitor material was prepared.

[0067] Through X-ray diffraction spectrum ( Figure 1 ), it can be determined that the diffraction peaks of the flower-shaped nickel hydroxide electrode material prepared in this comparative example are consistent with the standard spectrum of Ni(OH)2 (JCPDS No.38-0175).

[0068] Transmission electron microscopy (TEM) images ( Figure 3 ) showed that the prepared samples presented a flower ball morphology of uniform size, and these flower balls were assembled from lamellar structures.

[0069] Electrochemical tests of nickel hydroxide electrode materials such as Fig. 9 As shown in the figure, a and b are the CV and GCD test graphs of nickel hydroxide electrode materials, respectively. The CV curve shows a redox peak, indicating that a Faraday reaction occurs in the charge storage process of the electrode material. And as the current density increases, the GCD curve shows an obvious charge and discharge platform.

[0070] Comparative Example 2

[0071] A method for preparing a nickel molybdate nanotube supercapacitor electrode material, comprising the following steps:

[0072] Add 5 mL of N,N-dimethylformamide and 5 mL of anhydrous ethanol to a beaker and stir to dissolve at room temperature. Then add 5 mmol of citric acid and continue to stir to dissolve. Then add 1 mmol of ammonium molybdate and 1 mmol of nickel nitrate hexahydrate until they are completely dissolved. Add 1.0 g of polyvinyl pyrrolidone with a molecular weight of 1300,000 to the solution and continue stirring for 6 hours to prepare a spinnable precursor solution.

[0073] The prepared spinnable precursor solution was transferred to the electrospinning machine using a plastic syringe with a stainless steel needle. The electrospinning conditions were set as follows: the syringe needle was 18 cm away from the receiving plate, the room temperature was 25 °C, the voltage was 20 kV, and the solution ejection rate was 1.5 mL h -1 After electrospinning, the samples were placed in a muffle furnace for calcination. A two-step sintering procedure was set up, including calcination at 1 °C min -1 The temperature was raised to 300 °C at a heating rate of 1 °C min and maintained for 1 h. -1 The temperature was raised to 500°C at a heating rate and maintained for 1 h, and the obtained sample was the nickel molybdate electrode material.

[0074] The X-ray diffraction spectrum (XRD) of the nickel molybdate electrode material prepared in this comparative example is as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peak of the obtained product corresponds to the standard spectrum of NiMoO4 (JCPDS No.12-0348).

[0075] The scanning electron microscope (SEM) of the nickel molybdate electrode material prepared in this comparative example is as follows: Figure 2 As shown. Figure 2 It can be seen that the prepared samples are nanotubes with a diameter of about 200 nm.

[0076] Electrochemical tests of nickel molybdate electrode materials such as Fig.10 As shown in the figure, a and b are the CV and GCD test graphs of nickel molybdate electrode materials, respectively. The CV curve shows a redox peak, indicating that a Faraday reaction occurs in the charge storage process of the electrode material. And as the current density increases, the GCD curve shows an obvious charge and discharge platform.

[0077] Comparative Example 3

[0078] The method described in Example 1 is different from Example 1 in that the molar ratio of nickel molybdate, nickel nitrate hexahydrate, hexamethylenetetramine and sodium citrate is 2:1:1:0.1.

[0079] The electrochemical performance test shows that the material prepared in this ratio does not significantly improve the performance compared with Example 1. The specific results are shown in Fig.11 .

[0080] Comparative Example 4

[0081] The method for preparing the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material is carried out according to Example 1, except that:

[0082] In step (3), sodium citrate is not added, and a hydrothermal method is used, that is, 1.5 mmol nickel molybdate sample, 1.5 mmol nickel acetate, and 1.5 mmol HMTA are weighed, and stirred in a beaker containing 60 mL of aqueous solution at room temperature for 20 min, and heated to 95° C. for reaction for 12 h to obtain a sample. The obtained sample is washed with deionized water and ethanol three times each, and then placed in a 60° C. oven for drying for 12 h to obtain a nickel hydroxide-nickel molybdate nanotube composite material. The nickel hydroxide particles on the surface of the material are of different sizes and irregular shapes.

[0083] Comparative Example 5

[0084] The method for preparing the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material is carried out according to Example 1, except that:

[0085] Step (1), without adding citric acid,

[0086] In step (3), sodium citrate was not added and the rest was carried out as in Example 1.

[0087] A nickel hydroxide-nickel molybdate nanotube composite material is obtained, and the nickel hydroxide particles on the surface of the material are of different sizes and irregular shapes, and the particles are aggregated.

[0088] Application Experiment Example 1

[0089] 1. The nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material prepared in Example 1 was tested and compared with Comparative Example 1 and Comparative Example 2. The XRD spectrum is as follows: Figure 1 The scanning electron microscope image is shown in Figure 2 As shown, a represents the nickel molybdate electrode material, and b represents the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material prepared in Example 1. Figure 3 As shown, a represents nickel hydroxide electrode material, b represents nickel molybdate electrode material, and c represents the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material prepared in Example 1.

[0090] Figure 4-6The nitrogen adsorption and desorption and pore size distribution diagrams of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material prepared in Example 1 are shown respectively, and compared with Comparative Example 1 and Comparative Example 2, it can be seen that the specific surface area of ​​the sample in Example 1 is greatly improved. A three-electrode system is adopted, with the nickel hydroxide-nickel molybdate nanotube material prepared in Example 1 as the working electrode, the platinum electrode as the counter electrode, and the Hg / HgO electrode as the reference electrode, and the electrolyte used is a 3M KOH solution.

[0091] The electrochemical test comparison diagram of the nickel hydroxide electrode material of Comparative Example 1, the nickel molybdate electrode material of Comparative Example 2, and the nickel hydroxide-nickel molybdate nanotube electrode material prepared in Example 1 is shown in FIG. Figure 7 As shown, a, b, and c are performance comparison diagrams of three materials, a is a CV comparison diagram of the three materials, b is a GCD comparison diagram of the three materials at a specific current density, and c is a rate performance comparison diagram of the three materials, wherein A, B, and C are nickel molybdate, nickel hydroxide, and a composite material of nickel hydroxide and nickel molybdate, respectively. By comparison, it can be found that the unique nanosheet-nanotube structure of the nickel hydroxide-nickel molybdate nanotube electrode material prepared in Example 1 effectively increases the active specific surface area and mass transfer process, has a larger CV area, a higher specific capacity, and better electrochemical performance.

[0092] The CV and GCD test graphs of the nickel hydroxide-nickel molybdate nanotube electrode material prepared in Experimental Example 1 are as follows: Figure 8 As shown, a and b are CV and GCD test graphs of nickel hydroxide-nickel molybdate nanotube electrode materials, respectively.

[0093] Application Experiment Example 2

[0094] The specific capacity of the supercapacitor obtained by this experimental invention was tested, and the test results were as follows:

[0095] In 1Ag -1 The capacity of the supercapacitor of the present invention can reach 630C g -1 , at 5Ag -1 At a current density of , the specific capacity retention rate of the supercapacitor material of the present invention can reach 68%.

[0096] Application Experiment Example 3

[0097] A two-electrode system was adopted, with the supercapacitor material of Example 1 as the positive electrode material and activated carbon as the negative electrode material to form a hybrid supercapacitor, and the electrolyte used was a 3M KOH solution.

[0098] like Fig.12 As shown, in 2Ag -1 At a current density of , the capacity retention rate of the supercapacitor material of the present invention is 71.2% and the coulombic efficiency is 100%.

Claims

1. A method for preparing a nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material, comprising the following steps: (1) dissolving citric acid in a mixed solvent of N,N-dimethylformamide and anhydrous ethanol at room temperature, then adding nickel nitrate and ammonium molybdate, stirring until dissolved, and finally adding polyvinyl pyrrolidone (PVP), stirring for 6-12 hours, to obtain a precursor solution for spinning; (2) injecting the precursor solution into an electrospinning machine to prepare fibers by electrospinning, placing the obtained fibers in a muffle furnace for calcining, and cooling after the calcination to obtain nickel molybdate nanotube materials; (3) Dispersing nickel molybdate nanotube material in water, adding nickel acetate, hexamethylenetetramine (HMTA), and sodium citrate, mixing evenly, heating in a water bath for reaction for 4-12 hours, cooling, washing, and drying to obtain nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material.

2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of nickel nitrate to ammonium molybdate is (1-2): (1-2), and the volume ratio of the molar amount of citric acid to the mixed solvent is (4-6): (5-15), unit mmol mL -1 .

3. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of N,N-dimethylformamide to anhydrous ethanol is (1-2): (1-2).

4. The preparation method according to claim 1, characterized in that: In step (1), the weight average molecular weight of PVP (K90) is 1000,000-3000,000, and the molar ratio of the mass of PVP to ammonium molybdate is (0.8-1.5): (0.2-2), unit: g mmol -1 The molar ratio of nickel nitrate to the volume of the mixed solvent is (1-2): (8-12), unit: mmol mL -1 .

5. The preparation method according to claim 1, characterized in that: In step (2), the electrospinning conditions are: electrospinning temperature 22-28°C, voltage 18-22 kV, ejection rate 0.6-2.0 mL h -1 The calcination process is a two-step calcination process, specifically, first calcining at 0.5-2℃min -1 The heating rate is raised to 250-350℃, kept at this temperature for 0.5-2h, and then heated at 0.5-2℃min -1 The temperature is raised to 450-550°C at a heating rate and maintained for 0.5-3h.

6. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of the molar amount of nickel molybdate nanotube material to water is (0.5-1.5): 60mmol mL -1 .

7. The preparation method according to claim 1, characterized in that: In step (3), the molar ratio of nickel acetate, HMTA and sodium citrate is (1-2): (1-2): (0.05-1).

8. The preparation method according to claim 1, characterized in that: The molar ratio of nickel molybdate nanotube material to nickel acetate is 1:1, the water bath reaction temperature is 85-95°C, the water bath reaction time is 10-12h, the washing refers to washing with anhydrous ethanol for 3-5 times, and the drying is conventional drying.

9. A nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material, prepared by the method according to any one of claims 1 to 8.

10. Use of the nickel hydroxide-nickel molybdate nanotube supercapacitor electrode material according to claim 9 for preparing a supercapacitor as a working electrode of the supercapacitor.

Citation Information

Patent Citations

  • Preparation method of nickel molybdate / carbon electrode material and prepared supercapacitor

    CN110993364A

  • Nickel molybdate-nickel selenide-molybdenum selenide composite material and preparation method and application thereof

    CN112216521A